2020
DOI: 10.7759/cureus.11879
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) with Contrast-Induced Nephropathy in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Interventions

Abstract: Butt et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 23 publications
(32 reference statements)
5
31
1
Order By: Relevance
“…NLR, a relatively inexpensive marker of inflammation, has recently been explored as a predictor of mortality in patients who undergo percutaneous coronary intervention and can aid in the risk stratification and prognosis of patients diagnosed with acute coronary syndromes [ 21 ]. Moreover, NLR is an independent predictor of contrast-induced acute nephropathy in patients with acute myocardial infarction [ 22 ]. Remarkably, Lattanzi found that higher NLR levels upon admission were independently associated with poor outcomes at 30 days after the acute intracerebral hemorrhage onset [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLR, a relatively inexpensive marker of inflammation, has recently been explored as a predictor of mortality in patients who undergo percutaneous coronary intervention and can aid in the risk stratification and prognosis of patients diagnosed with acute coronary syndromes [ 21 ]. Moreover, NLR is an independent predictor of contrast-induced acute nephropathy in patients with acute myocardial infarction [ 22 ]. Remarkably, Lattanzi found that higher NLR levels upon admission were independently associated with poor outcomes at 30 days after the acute intracerebral hemorrhage onset [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of a particular lineage of immune cells, such as neutrophils, monocytes, and lymphocytes, occurs during revascularization and has a detrimental effect on long-term prognosis [ 47 , 48 , 49 , 50 ]. The simple counts of neutrophils and monocyte-to-lymphocyte ratio were proposed as prognostic markers [ 51 , 52 , 53 , 54 , 55 ]. The perioperative inflammatory reactions, presented as the ratios mentioned above, were associated with long-term surgical revascularization results [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratios per unit increase in the average NLR (log) increased by 1.06 ( p = 0.0133) and 1.09 ( p = 0.0006), respectively ( 54 ). Butt et al ( 55 ) showed that a high NLR is an independent predictor of contrast-induced acute nephropathy in patients with acute myocardial infarction (AMI) (OR 2.03, 95% CI: 1.403–3.176, P <0.001).…”
Section: Discussionmentioning
confidence: 99%